Three-Dimensional Printed Model of the Mediastinum for Cardiothoracic Surgery Resident Education - Catherine T. Byrd, MD; Winston L. Trope, BE; H. Henry Guo, MD, PhD; Kyle Gifford, BA; Prasha Bhandari, MPH; Jalen Benson, AB; Douglas Z. Liou, MD; Leah M. Backhus, MD, MPH; Mark F. Berry, MD; Joseph B. Shrager, MD; Natalie S. Lui, MD, MAS (Annals of Thoracic Surgery Short Reports, 2025)
Background: Mediastinoscopy remains an important component of lung cancer staging. The development of endobronchial ultrasonography has meant residents perform fewer mediastinoscopies. We hypothesized that a 3-dimensional printed model of the mediastinum would be an effective tool for teaching residents the anatomy and techniques for mediastinoscopy. Methods: A color model of the mediastinum was 3-dimensionally printed based on segmented computed tomographic images. For 2 years, residents and attendings were asked to provide a skills assessment after every mediastinoscopy. During the second year, all residents received standardized instruction for mediastinoscopy using the 3-dimensional model. Skills assessments were compared between the residents taught with and without the 3-dimensional model. Results: There were 49 resident and 65 attending surveys completed. Residents taught with the 3-dimensional model were more likely to answer that they could identify normal anatomy “well”/“very well” compared with residents taught without the model (86% vs 52%, P = .015). Residents taught with the 3-dimensional model more frequently answered they were able to perform an uncomplicated mediastinoscopy “well”/ “very well” (59% vs 31%, P = .079) compared with residents taught without the 3-dimensional model, although this was not significant. Attendings were equally likely to answer “well”/“very well” that residents taught with the 3-dimensional model could identify normal anatomy (52% vs 55%, P > .99) and perform an uncomplicated mediastinoscopy (48% vs 43%, P = .79) compared with those taught without the model. Conclusions: A 3-dimensional printed model of the mediastinum may be an effective tool for teaching mediastinoscopy.